Comparative Analysis of Tonal Systems in Chinese and Thai and Teaching Strategies for Chinese Tonal Patterns - Aroonawongsa, Supaporn; Juraiyanon, Pornpen; Larblerd, Thanuttha (Rajamangala University of Technology Tawan-ok Social Science Journal, 2025)
Thai and Chinese are both tonal languages. Compared with Chinese learners in non-tonal language areas, Thai students can learn Chinese tones relatively easily. However, in my teaching practice, I found that a large number of Thai Chinese learners exhibit the phenomenon of "foreign tones." This study conducts a comparative analysis of Chinese and Thai tonal systems through classroom observation and phonetic comparison, identifying the causes of tonal errors among Thai learners. Based on the analysis, specific teaching strategies, such as gesture-assisted learning and modified tonal teaching sequences, are proposed. The effectiveness of these strategies is supported by pre and post-test results from classroom implementation. The findings highlight the importance of addressing tonal differences in teaching Chinese to Thai learners.